Prisoners of the ghostland [videorecording (Blu-Ray)] - Sono, Sion, 1961-; Cage, Nicolas, 1965-; Boutella, Sofia, 1982-; Cassavetes, Nick (Image Entertainment, 2021)
A criminal must break an evil spell in order to rescue a girl who has mysteriously disappeared.